2011
DOI: 10.1111/j.1399-0004.2011.01689.x
|View full text |Cite
|
Sign up to set email alerts
|

Fabry disease: polymorphic haplotypes and a novel missense mutation in the GLA gene

Abstract: Fabry disease: polymorphic haplotypes and a novel missense mutation in the GLA gene. Fabry disease (FD) is an X-linked lysosomal storage disorder with a heterogeneous spectrum of clinical manifestations that are caused by the deficiency of α-galactosidase A (α-Gal-A) activity. Although useful for diagnosis in males, enzyme activity is not a reliable biochemical marker in heterozygous females due to random X-chromosome inactivation, thus rendering DNA sequencing of the α-Gal-A gene, alpha-galactosidase gene (GL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 39 publications
3
22
0
1
Order By: Relevance
“…Of interest, we also observed that as much as the 22.4% of the whole dialysis population displays intronic polymorphisms of the GLA gene [20] which is a prevalence significantly higher than that registered in the corresponding general population. Even though some studies try to associate these intronic mutations in GLA gene with Fabry disease [28], the involvement of intronic mutation in Fabry disease remains unclear.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Of interest, we also observed that as much as the 22.4% of the whole dialysis population displays intronic polymorphisms of the GLA gene [20] which is a prevalence significantly higher than that registered in the corresponding general population. Even though some studies try to associate these intronic mutations in GLA gene with Fabry disease [28], the involvement of intronic mutation in Fabry disease remains unclear.…”
Section: Discussionmentioning
confidence: 83%
“…In 55 of 227 patients (24.2%), we found mutations in non-coding GLA regions, the most of those are grouped in aplotypes (Table 3) [20]. In all of these patients, the analysis of enzymatic activity was inside the normal range.…”
Section: Intronic Mutationsmentioning
confidence: 96%
“…ncbi.nlm.nih.gov/nuccore/NM_000169.2; National Library of Medicine, Bethesda, MD, USA). Three single nucleotide polymorphisms (SNPs) respectively identified by reference numbers rs2071225, rs3027585 and rs3027584 at the NCBI SNP database (dbSNP, http://www.ncbi.nlm.nih.gov/snp/), which result from cytosine-to-thymine (C>T) or adenineto-guanine (G>A) transitions at cDNA nucleotide positions c.-10(C>T), c.-12(G>A) and c.-30(G>A), counting backwards from the translation initiation codon, are relatively common in several ethnically different populations (Davies et al 1993;Saifudeen et al 1995;Wu et al 2011;Ferri et al 2012), including the Portuguese (Oliveira et al 2008a). The dbSNP lists three additional GLA 5 0 UTR SNPs, at positions c.-8(C>G), c.-18(T>C) and c.-105(A>G), respectively identified as rs371291716, rs545597063 and rs3027583, but these variants have never been reported in the Portuguese population.…”
Section: Introductionmentioning
confidence: 99%
“…To date, more than 600 pathogenetic mutations (missense, nonsense, and splice site point mutations and 'short length' rearrangements such as deletions and duplications) and up to 14 DNA polymorphisms have been reported [2] .…”
Section: Discussionmentioning
confidence: 99%